Breast cancer detection using charge sensors coupled to DNA monolayer. Issue 1793 (2015) - Batistuti, Marina R.; Mulato, Marcelo; Bueno, Paulo R.
ABSTRACT: We report the development of a label-free biosensors based on DNA hybridization, using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). This study uses DNA sequences based on microRNA related with breast cancer. The biosensor was fabricated by immobilizing a self-assembled monolayer of single-stranded 23-mer oligonucleotide (ss DNA) via a thiol linker on gold work electrodes. Residual binding places were filled with 6 -mercaptohexanol (MCH). The electrode was electrochemicaly characterized in the presence of a redox system ferri/ferrocyanide. Different concentrations of complementary DNA sequence for hybridization were incubated; an increase of charge transfer resistance (Rct ) was observed, used as sensor parameter and correlated with concentrations of complementary DNA sequence. A debate was presented on the effect of the MgCl2 influence onss DNA immobilization solution.